PROFIL KEPALA SEKOLAH DASAR - Agustian Agustian (Manajer Pendididikan, 2016)
The general objective of this study was to describe the profile of Elementary School Principals at District of East Curup. In this study also uses qualitative descriptive method becauseresearchers wanted to describe and interpret objects in accordance with the actual situation. The results of this study concluded that: 1) educational qualifications Elementary School Principal se subdistrict East Curup have met the criteria and requirements as the principal, although there is notyet, but in the settlement, 2) experience the Principal is enough, 3) the principal's own good competence, 4) years of service principals that have no more than one period and some are not quite the period, 5) the principal has also been able to resolve the problems it faces.Keywords: profile, principal